Non‐randomized studies should be considered for assessing surgical techniques in rectal prolapse: prospective cohort study. (18th October 2020) - Lee, M. J.; Dimairo, M.; Edwards, J; Hawkins, D. J.; Hind, D.; Knowles, C. H.; Hooper, R.; Brown, S. R.; ,
Abstract: Aim: Randomized trials comparing surgical techniques for rectal prolapse are not always feasible. We assessed whether non‐randomized comparisons of those who have had surgery with those still waiting would be confounding baseline health status. Method: This was a prospective cohort study in seven UK hospitals. Participants were ≥ 18 years and listed for surgical interventions of equivalent intensity for rectal prolapse. They were defined as short or long waiters (≤ 18 or > 18 weeks, respectively). Time on the waiting list was compared with baseline comorbidity (Charlson comorbidity index) and change from baseline in health status (EQ‐5D‐5L) at the time of surgery. Results: In all, 203 patients were analysed. Median (interquartile range) waiting time was 13.7 weeks (8.1, 20.4) varying across sites. Baseline comorbidity was not an important predictor of waiting time. Median Charlson comorbidity index was 2 (0, 3) for short and 1 (0, 3) for long waiters. A change in waiting time by a week was associated with negligible improvement in the EQ‐5D‐5L index of 0.001 (95% CI −0.000 to 0.003, P  = 0.106). Conclusion: Negligible change in patient reported health status while on the waiting list and lack of effect of comorbidities in influencing waiting time support the use of non‐randomized pre‐/post‐studies to compare the effects of surgical interventions for rectal prolapse.